Can the gap get any wider? How the new GCSE curriculum will make progression to university more challenging and less inclusive. Issue 2 (4th March 2022) - Cazzoli, Marcela A.
ABSTRACT: The latest reforms to the GCSE Subject Content attempt to bring languages in line with other subject areas through a quantification of the material that needs to be learnt and a focus on the linguistic system, to the detriment of the broader communicative aims associated with 'knowing a language'. This article suggests that the reforms expose a lack of understanding of the fact that curricula based on instrumental skills do not prepare students (from state schools, in particular) for the level of reflection and intellectual enquiry that is at the core of university learning. This paper will also argue that an instrumental view of languages creates a wider gap between school and university that perpetuates inequality and that keeps promoting an Anglocentric public idea about languages. In order to mitigate the impact of the latest GCSE reforms, it is proposed that higher education institutions and schools should engage in collaborative work towards an understanding of language education that takes account of some of the principles which now inform languages curriculum reform in higher education in the UK and also in other sectors in Europe via the CEFR.